Léxico e identidade: as expressões idiomáticas do povo brasileiro - Gabaldi, Elza de Fátima (2012)
This Dissertation - located at the interface between studies conducted in the field of lexicology focused on the research of History and Description of the Portuguese Language Program at Postgraduate Studies at the Catholic University of Sao Paulo - thematizes the general vocabulary of the language itself, focusing on its own so-called idioms expressions. The topic has been subjected to different and varied research, which provided significant contributions to the researchers in how understand the functionality of the research in the field of translation, production of bilingual dictionaries, and for teaching Portuguese for foreign speakers, and also how they are explained as a product of metaphorical constructions. Thus, the overall goal was to extend understanding of these processes to situate them as lexical-grammatical elements from Portuguese language vocabulary, which has been pointing out that idiomatized language by contacts between people from different cultural environments, the flowing of construction of similar stories that entered the cultural nuances of these differences, contributes for the language construction. This understanding has turned to issues in which / through the lexicon it is possible to recognize the cultural identity of a people. This goal of a general nature was developed based on three specific objectives, qualified as possible to be measured by results of analyzes. In the Chapter I, we mentioned issues about variations and varieties of the Portuguese language uses, guided by a historical point of view, to differentiate historical language - standards socio-historical-cultural rules - language system, placing the language regarding the architecture March to the formation of Brazilian culture. In the second chapter, we sought to differentiate, for review procedures, assumptions regarding lexicultura oriented, the distinction between types of composite lexias whose lexical forms are identical as regards the language system, but the contents of their lexical meanings differ as to use by Brazilian and Portuguese Iberian and can only be explained by a socio-cultural-historical. We gave it emphasis on strategies regarding the procedures as they are idiomatizadas by Brazilians. In the third chapter - to understand the crystallization processes by which these lexias are called, the results indicated that the crystallization result of morphological constraints and not the processes of composition of their meanings, which is why they are continuously ressemantizadas-discursive and textual resources through language practices so as to give the old with the new resemantization